CHARACTERIZATION OF THE ELECTROPHYSICAL PROPERTIES OF SILICON-SILICON DIOXIDE INTERFACE USING PROBE ELECTROMETRY METHODS - V. А. Pilipenko; V. A. Saladukha; V. A. Filipenya; R. I. Vorobey; O. K. Gusev; A. L. Zharin; K. V. Pantsialeyeu; A. I. Svistun; A. K. Tyavlovsky; K. L. Tyavlovsky (Приборы и методы измерений)
Introduction of submicron design standards into microelectronic industry and a decrease of the gate dielectric thickness raise the importance of the analysis of microinhomogeneities in the silicon-silicon dioxide system. However, there is very little to no information on practical implementation of probe electrometry methods, and particularly scanning Kelvin probe method, in the interoperational control of real semiconductor manufacturing process. The purpose of the study was the development of methods for nondestructive testing of semiconductor wafers based on the determination of electrophysical properties of the silicon-silicon dioxide interface and their spatial distribution over wafer’s surface using non-contact probe electrometry methods.Traditional C-V curve analysis and scanning Kelvin probe method were used to characterize silicon- silicon dioxide interface. The samples under testing were silicon wafers of KEF 4.5 and KDB 12 type (orientation <100>, diameter 100 mm).Probe electrometry results revealed uniform spatial distribution of wafer’s surface potential after its preliminary rapid thermal treatment. Silicon-silicon dioxide electric potential values were also higher after treatment than before it. This potential growth correlates with the drop in interface charge density. At the same time local changes in surface potential indicate changes in surface layer structure.Probe electrometry results qualitatively reflect changes of interface charge density in silicon-silicon dioxide structure during its technological treatment. Inhomogeneities of surface potential distribution reflect inhomogeneity of damaged layer thickness and can be used as a means for localization of interface treatment defects.